Tematyka kulinarna w literaturze polskiej XX wieku - Mielżyńska, Agnieszka (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2009)
The article is based on chosen examples from Polish poetry and prose of the XXth century. The first subchapter “Picnic cuisine” depicts a picnic, described by Tuwim in Kwiaty polskie. The sreond subchapter “Sentimental cuisine” based on Tuwim’s poetry, highlights the role of smell and taste in creating the most beautiful childhood memories. The last part “Borderland cuisine” based on prose (Cz. Miłosz, T. Konwicki, T. Lubkiewicz-Urbanowicz), shows sentimental journey following the various tastes of Wilno.